Recent Energy Trends in India - Umanand Kumar Singh; Kushal Sharma (AG Volumes, 2021)
Today in the professional world energy consumption is the most important factor for a progressive and developed nation in the world. Presently India is the 3rd largest producer as well as consumer of power generation & one of the most powerful progressive nations in the world. Most of the countries in the world change their thinking in terms of power generation from conventional energy to renewable energy like Solar, Wind, Geothermal, Small Hydel power, etc. Recently in India, power generation from conventional types of energy like fossil fuel gradually decreased and power generation from renewable energy rapidly increased in the last few years. Now a day’s every sector in India slowly increasing its dependency on renewable energy sources in concern of depleting conventional energy sources and protecting its climate.